Infant Feeding Practices among Mothers Attending Kanti Children’s Hospital, Kathmandu - Bastola, Sanjita; Chaudhary, Tanuja Kumari; Lawat, Isabel (Journal of Nursing Education of Nepal, 2022)
Background: Appropriate feeding practices improve health, reduce disease burden and malnutrition. One-third of cases of malnutrition are caused by inappropriate infant feeding, which is one of the world’s biggest issues. The objective of this study was to find out the infant feeding practices among mothers attending Kanti Children Hospital in Kathmandu. Methods: A descriptive, cross-sectional research design was used to conduct this study. The study was carried out at Kanti Children’s Hospital, Kathmandu. A non-probability convenience sampling technique was adopted to select 180 respondents. A semi-structured interview schedule was used to collect the data. Descriptive statistics (frequency, percentage, mean, and standard deviation) were used to describe the socio-demographic characteristics of mothers and infants. The inferential statistic (chi square test) was used to determine the relationship between infant feeding practice level and selected variables. Results: The study’s findings revealed that most (91.1%) respondents had good infant feeding practices. More than half (56.9%) of respondents had initiated breastfeeding within one hour of delivery. The most of infants (95.6%) were given colostrum milk. Very few (2.7%) of respondents had given prelacteal feeding to their babies. More than half of respondents (58.9%) had done exclusive breastfeeding, and 54.4% began weaning at six months. Most (75.5%) infants were given dal, rice, or jaulo as their primary food among the complementary foods. Similarly, almost half (42.8%) of babies received their meals at the recommended intervals. Conclusion: Most of the mothers practiced good infant feeding habit. Only few mothers had tried prelacteal feeding. One-third of the infants were bottle-fed. Nearly half of mothers began complementary feeding before six months. It is therefore advised to continue raising awareness about good feeding practices for infants. Emphasis should be given to educating mothers about complementary feeding practices. Keywords: Colostrum, Exclusive Breast Feeding, Infant, Weaning